Indicadores bibliométricos da produção científica em educação especial : estudo da Revista Educação Especial (2000-2006) - Silva, Rosemary Cristina da (2008)
The broad scope of Special Education and its interfaces with other fields of knowledge can be attested by the comprehensiveness of scientific production found in Brazilian and international academic journals. This work depicts a bibliometric study of a Brazilian scientific journal in the field of Special Education, i.e., Revista Educação Especial, chosen due to its being the most long-standing journals in this field in the country. This study analyzed issues published from 2000 to 2006, including those published on line, totaling 14 issues or 147 articles. The goal was to identify, by means of categorization, the topics of the articles and the geographical origin of their authors, classify the articles belonging to the core of this field and those pertaining to secondary and peripheral areas. The results, analyzed by means of bibliometric data treatment and analysis tools, showed the following aspects regarding the articles: the most productive authors were Reinoldo Marquezan, Soraia Napoleão Freitas, Maria Inês Naujorks, Eduardo Zevallos Ayala, Vera Lúcia Marostega and Hugo Otto Beyer; the most representative geographical origin was Universidade Federal de Santa Maria (South of Brazil); most articles were authored by two or more researchers; original articles represented 70.7% of the scientific production; and the most common keyword was Inclusion . With respect to the literature referenced in these articles, the results indicated that: books made up the greater part of the references; the source updating level was satisfactory: the most used language was Portuguese; the predominant format was print; the most influential authors were Brasil, Vygotsky, Freire, Skliar and Foucault; the core of the journal was confirmed to be within the field of Special Education whereas its secondary and peripheral areas were Education, Pedagogy and Psychology. It is hoped that these indicators may contribute to the evaluation of the state of the art in Special Education as well as facilitate the dissemination of research carried out in this field of knowledge